Effects Of Computer-Based Testing Feedback On Students' Achievement And Errors In Algenbraic Expressions - Chin, Sook Fui (2017)
Algebra is a branch of mathematics that substitutes letters for numbers. It is the gatekeeper course to advanced study in mathematics. However, students always face difficulty and have misconceptions in learning algebraic expression and it influences their cognitive development. Meanwhile, educational technology has served as an important tool in improving teaching and learning process, including computer-based testing (CBT), which students can be accessed and receive valuable timely feedback on their performance. This study aimed to determine the effects of computer-based testing (CBT) feedback on students’ achievement and errors in algebraic expressions.